2019
DOI: 10.1016/j.jappgeo.2019.05.008
|View full text |Cite
|
Sign up to set email alerts
|

2D-ERT monitoring of soil moisture seasonal behaviour in a river levee: A case study

Abstract: We present a study of the seasonal behaviour of soil moisture in an old embankment levee by means of 2D DC-electrical resistivity tomography monitoring based on an embedded electrode installation. We were able to produce seasonal resistivity change models that are compensated for temperature effects using a seasonal temperature profile model. Time-lapse sections of percentage resistivity changes show spatial and temporal overall consistency with seasonal variations of soil temperature. Discrepancies are likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…In the last 20 years, more than 200 papers have been published on ISI journals (Figure 1). The TL-ERT method found an impressive number of applications crossing different disciplines, from hydrogeology [9][10][11][12] to agriculture [13][14][15][16], from engineering geology [17][18][19][20] to geohazards [21][22][23][24], from CO2 storage [25] to the study of the effects of the climate changes on soil and near subsurface [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…In the last 20 years, more than 200 papers have been published on ISI journals (Figure 1). The TL-ERT method found an impressive number of applications crossing different disciplines, from hydrogeology [9][10][11][12] to agriculture [13][14][15][16], from engineering geology [17][18][19][20] to geohazards [21][22][23][24], from CO2 storage [25] to the study of the effects of the climate changes on soil and near subsurface [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The Ground Penetrating Radar (GPR), for instance, has proven to be an efficient method to determine the thickness of buried structures, whether natural or anthropic, such as crypts or tombs, or to detect boundaries between different building materials (Goodman, D., 1994;Carcione, J.M., 1996;Jol, 2009;Johnston et al, 2018;Yalçıner, 2019). Electrical resistivity tomography (ERT) has also been successfully tested in archaeological surveys due to its high sensitivity (Gündgdu, et al, 2017;Jodry et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been acknowledged as a valuable tool for monitoring water flow in flood prone areas (Brunet, et al, 2010) and it has recently found applications in the monitoring of water content in flood embankments. It can be conveniently implemented to investigate seasonal variations of water regime as a permanent monitoring system by burying the electrodes in the soil and transferring the data remotely, to correlate water content variation to weather events and parameters (Tresoldi, et al, 2019); (Jodry, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Interpretation of ERT results can be complicated and affected by uncertainties for several reasons, including anomalies in the resistivity due to improper contact between electrodes and ground surface (Jodry, et al, 2019), numerical artefacts generated during the inversion process and effects of three-dimensional structures in the survey areas which cannot be accounted for in a two-dimensional model (Hojat, et al, 2020). Moreover the resistivity values are influenced by other variables (e.g.…”
Section: Introductionmentioning
confidence: 99%